Effect Of Accessibility And Assembly Method To Product Or System Maintainabilty - Hasim, Mohd Hasrul (Universiti Sains Malaysia, 2005)
This thesis is an outcome from a research on the effect of accessibility and assembly method to maintainability. This research is done based on some factors and elements that involved in maintainability process. A survey on customers and motorcycle mechanics to get their feedback on motorcycle maintenance that focus on the former brake system. Besides that an experimental work is done based on the brake system that have been built using the experimantal tools. The experiment is done to observe the factors that effect the brake system maintainability The fisrt step to make the system model is to make the frame. Then the brake system is jointed to the frame. A test has been done to the brake system model and by recording a time on different person in maintenance work done for the brake system. From the survey and experimental work done for this research, it is concluded that the brake drum design and skills level of a person are the major factor that effect maintainability. Other factor such as the component brand, tools that used, spare part used, spring attached also gives a minor effect on maintainability.